أثر بعض المتغيرات الكينماتيكية على دقة الإرسال في التنس الأرضي - الحراحشة، قتيبة أحمد قسيم; الخزاعلة، بشار أحمد; الحمدون، منصور نزال (جامعة آل البيت, 2022)
هدفت الدراسة التعرف إلى أثر بعض المتغيرات الكينماتيكية على دقة الإرسال الساحق في التنس الأرضي. واستخدمت الدراسة المنهج الوصفي بصورة العلاقات الارتباطية، حيث تكونت العينة من (10) لاعبين من لاعبي المنتخب الوطني للتنس الأرضي، وتم اعتماد المتغيرات الكينماتيكية (زاوية المرفق، زاوية الرسغ، زاوية الكتف، سرعة الكرة، زاوية ميل الجذع، زاوية الركبة، زاوية انطلاق الكره). واستخدم الباحثون كاميرا تصوير فيديو رقمية نوع (Nikon) عدد (1) ذات سرعة (50) صورة ثانية، وأظهرت النتائج أن جميع المتغيرات الكينماتيكية التي طبقت على عينة الدراسة كانت دالة إحصائيا عند مستوى الدلالة (0.05) المرتبطة بدقة الإرسال الساحق، كما أظهرت أيضا أن هناك تسلسل في الانتقال الحركي وبشكل متناسق وانسيابي من أسفل الجسم وصولا إلى لحظة ضرب الكرة مما أثر بشكل إيجابي على سرعة الكرة وبالتالي أصبح التحكم بدقة واتجاه الكرة أكبر. The aim of the study was to identify the impact of certain kinematic variables on the accuracy of the overwhelming transmission in ground tennis. The study used the descriptive correlative approach. The sample of the study consisted of (10) players from the national ground tennis team. The Kinematic variables including (elbow angle, wrist angle, shoulder angle, ball velocity, trunk tilt angle, knee angle, the kicking angle) were used. The researchers used one digital camera (Nikon) with a speed of (50) images/ sec. The results of the study showed that all the kinematic variables applied on the sample of the study were statistically siginificant at (α≤0.05) associated with the accuracy of the overwhelming transmission. The results as well showed that there is a sequence in the spinning transmission in a harmonic way: from the bottom of the body to the moment of kicking the ball, which positively impacted the velocity of the ball, and in turn, the control over the accuracy and the direction of the ball became greater.
Keywords: الأداء الحركي -- مهارات الإرسال -- القدرات العضلية -- رياضة التنس